Lactobacillus helveticus and Lactobacillus plantarum modulate renal antioxidant status in a rat model of fructose-induced metabolic syndrome - Korkmaz, Ömer Adil; Sadi, Gökhan; Kocabaş, Aytaç; Yildirim, Onur Gökhan; Sumlu, Esra; Koca, Halit Buğra; Nalbantoglu, Barbaros; Pektaş, Mehmet Bilgehan; Akar, Fatma (Archives of Biological Sciences, 2019)
Paper description: Dietary high-fructose causes metabolic disorder and augments the risk of chronic kidney diseases most probably due to oxidative stress. Renal superoxide dismutases are suppressed while catalase is upregulated in fructose-fed rats. Lactobacillus helveticus and Lactobacillus plantarum alleviate dietary fructose-induced changes in biochemical markers of blood and renal antioxidant enzymes. Lactobacillus helveticus and Lactobacillus plantarum might have a positive influence on renal antioxidant capacity in the dietary fructose-induced metabolic disorder. Abstract: High dietary fructose intake causes a metabolic disorder and augments the risk of chronic kidney disease most likely due to oxidative stress. Probiotics could have antioxidant, antiinflammatory and immunoregulatory properties. The present study examined the influence of Lactobacillus helveticus and Lactobacillus plantarum supplementation on dietary fructose-induced metabolic changes and renal antioxidant/oxidant status of rats. Male Wistar rats were divided into four groups as follows: control; fructose; fructose plus L. helveticus; fructose plus L. plantarum. Fructose was given to the rats as a 20% solution in drinking water for 15 weeks. The probiotic supplementation was applied by gastric gavage once a day for six weeks. Several metabolic parameters in the plasma, gene and protein expressions of the main antioxidant enzymes in renal tissues of rats were measured. Dietary fructose-induced elevations in plasma insulin, triglyceride, VLDL, creatinine as well as renal urea levels were alleviated after treatment with L. helveticus and L. plantarum. Moreover, L. helveticus and L. plantarum supplementation recovered the changes in renal protein expression level of SOD1, SOD2 and CAT. In conclusion, supplementation with L. helveticus and L. plantarum has an improving effect on specific metabolic parameters and renal antioxidative enzymes in a fructose-induced metabolic disorder. https://doi.org/10.2298/ABS190123008K Received: January 23, 2019; Revised: February 20, 2019; Accepted: February 21, 2019; Published online: February 26, 2019 How to cite this article: Korkmaz OA, Sadi G, Kocabas A, Yildirim OG, Sumlu E, Koca HB, Nalbantoglu B, Pektas MB, Akar F. Lactobacillus helveticus and Lactobacillus plantarum modulate renal antioxidant status in a rat model of fructose-induced metabolic syndrome. Arch Biol Sci. 2019;71(2):265-73.